Entrepreneur intention: a study among students of higher institutions in UiTM Bandaraya Malacca / Muhammad Ikhmal Zulkifli and Nur Nurul Naim Che Md Akhir - Zulkifli, Muhammad Ikhmal; Che Md Akhir, Nur Nurul Naim (Faculty of Business and Management, Universiti Teknologi MARA, 2014)
There are many ways to attract youth in starting a venture. Various programmers has been adapted by the government and NGOs to attract youth of entrepreneurship. However, one of the constraints that youth face in entrepreneurship is the certainty to succeed in long term. Potential entrepreneurs are crucial as they will assist or inherit the present entrepreneurs in Malaysia’s industries. Other than that, youth are lacking in knowledge of protecting their business. 95% of students wanted to start a business but 76% doesn’t know how to protect it. With this, their entrepreneur intention decreases as they are unwilling to suffer the consequences bankruptcy. Many factors that influence entrepreneur intentions. Firstly is social norms which means the surrounding factors that influence us. Family, friends, work colleagues are the closest that can influence us in becoming an entrepreneur. Secondly is, Education system which means providing motivation, knowledge and skills essential for launching a successful business venture. Thirdly is economic pressure which means the difficulties in daily financials. High economic pressure means that students must find ways to increase their income. Lastly is risk taking which means whether students are risk taker or risk averse, it will affect the students’ entrepreneurship intentions.